Effect of ceramic filler-containing polymer hydrogel electrolytes coated on the polyolefin separator on the electrochemical properties of activated carbon supercapacitor - Kim, Kwang Man; Latifatu, Mohammed; Lee, Young-Gi; Ko, Jang Myoun; Kim, Jong Huy; Cho, Won Il (SPRINGER, 2014)
Hydrophobic polyolefin (polyethylene and polypropylene) separators are modified to encompass hydrophilicity on their surfaces through sulfonation, and then coated by polymer hydrogel electrolyte composed of 6 M KOH, potassium polyacrylate (PAAK) (1.5 wt.%), and the ceramic nanoparticles (10 wt.%) of SiO2, TiO2, and Al2O3. The ceramic filler-coated sulfonated polyolefin separators are applied to a supercapacitor with two symmetric activated carbon electrodes. The supercapacitors with the sulfonated polyolefin separators coated with ceramic filler-PAAK hydrogel electrolytes exhibit superior electrochemical performance, especially in the high scan rate region, compared to the case of coating the pure PAAK hydrogel electrolyte without ceramic fillers. In particular, the PAAK hydrogel electrolyte with SiO2 contributes to a higher specific capacitance at a high scan rate due to the strong hydrophilicity originated from both the sulfonated separator surfaces and the SiO2 nanoparticles.
Keywords: POLYPROPYLENE; SULFONATION; MEMBRANES; BATTERIES